Penerapan Metode Single Exponential Smoothing Pada Peramalan Penjualan Di UD. Kaya Rasa Berbasis Web - Prasetyo, Hafedo Rakhmad; Eka Purwiantono, Febry (J-INTECH (Journal of Information and Technology), 2023)
This research was conducted to help forecast the sales of cakes and foods at UD. Kaya Rasa, which fluctuates and experiences varying sales volumes in each sales period. Based on the aforementioned problem, a system is needed to forecast the sales of cakes and foods, namely Single Exponential Smoothing (SES). This research uses the SDLC Waterfall model for system development, while the application will be web-based using the CodeIgniter framework. Black box testing is conducted for system testing. The result of this research is a web-based forecasting application that can predict the sales of cakes and food in the next period based on actual sales data from the previous period. As a result, UD. Kaya Rasa can accurately estimate sales and sales profits for the next period using the SES formula.